PHYTOCHEMICAL SCREENING AND ANTIMICROBIAL PROPERTIES OF MEDICINAL PLANTS - Anil Kumar (The Bioscan, 2025)
Medicinal plants have historically been considered as a very important source of therapeutics, especially because of the availability of bioactive phytochemicals. These are natural products that have been extensively researched due to their possible therapeutic pharmacology to humans because of their important defense roles in the plants. With the development of antimicrobial resistance, finding new sources of antimicrobial compounds synthesized by plants has taken serious consideration. Phytochemical screening is major tool in the assessment of occurrence of such compounds whereas antimicrobial testing also determines the therapeutic value of plant extracts against the pathogen microorganisms. This paper provides a secondary thematic approach to reviewing literature to analyze phytochemical composition and antimicrobial activity of medicine plants. The aim is to reveal the prevalent classes of phytochemicals in medicinal plants, investigate their antimicrobial activity and get the synthesis of thematic findings of different studies. Secondary data was systematically collected, coded, and thematically analyzed to identify recurring patterns and insights. The analysis revealed four major themes: diversity and richness of phytochemicals, plant-specific antimicrobial efficacy, synergistic potential with conventional antibiotics, and ethnomedicinal significance. Alkaloids, flavonoids, tannins, saponins, and phenolic compounds emerged as the most commonly identified phytochemicals. Several plant species demonstrated significant antimicrobial activity, particularly against resistant strains of Staphylococcus aureus, Escherichia coli, and Candida albicans. This study underscores the therapeutic potential of phytochemical-rich medicinal plants and highlights the importance of integrating traditional knowledge with modern screening techniques. The findings support further research into plant-based antimicrobial agents as viable alternatives or complements to synthetic drugs. KEYWORDS: Medicinal plants, Phytochemical screening, Antimicrobial properties, Secondary, data analysis, Thematic synthesis, Traditional medicine, Bioactive compounds.